(untitled) (London, 2010)
Beyond Naturalness brings together leading scientists and policymakers to explore the concept of naturalness, its varied meanings, and how managers should intervene in ecosystem processes to protect park and wilderness values.
Keywords: Các khu bảo tồn,Protected areas,Ecosystem management,Nature conservation,Quản lý hệ sinh thái,Bảo tồn thiên nhiên; Quản lý,Management; Hoa Kỳ,United States,United States,United States,Hoa Kỳ,Hoa Kỳ